Controlled release of drugs in electrosprayed nanoparticles for bone tissue engineering - Jayaraman, Praveena (2016)
Generating porous topographic substrates, by mimicking the native extracellular matrix (ECM) to promote the regeneration of damaged bone tissues, is a challenging process. Generally, scaffolds developed for bone tissue regeneration support bone cell growth and induce bone-forming cells by natural proteins and growth factors. Limitations are often associated with these approaches such as improper scaffold stability, and insufficient cell adhesion, proliferation, differentiation, and mineralization with less growth factor expression. Therefore, the use of engineered nanoparticles has been rapidly increasing in bone tissue engineering (BTE) applications. The electrospray technique is advantageous over other conventional methods as it generates nanomaterials of particle sizes in the micro/nanoscale range. The size and charge of the particles are controlled by regulating the polymer solution flow rate and electric voltage. The unique properties of nanoparticles such as large surface area-to-volume ratio, small size, and higher reactivity make them promising candidates in the field of biomedical engineering. These nanomaterials are extensively used as therapeutic agents and for drug delivery, mimicking ECM, and restoring and improving the functions of damaged organs. The controlled and sustained release of encapsulated drugs, proteins, vaccines, growth factors, cells, and nucleotides from nanoparticles has been well developed in nanomedicine. This review provides an insight into the preparation of nanoparticles by electrospraying technique and illustrates the use of nanoparticles in drug delivery for promoting bone tissue regeneration.